School-Based Study to Assess the Nutritional Status (BMI based) of Adolescents of Gojra City of District Toba Tek Singh, Punjab, Pakistan: School-Based Study to Assess the Nutritional Status - Perveen, Shagufta; Karmaliani, Rozina; Barolia, Rubina; Mistry, Rozina (Pakistan Journal of Health Sciences, 2023)
Adolescence is the make-or-break stage of life. Major physical, mental, and psychological growth takes place at this age. Adequate and balanced nutrition is a vital requirement to support this phase. Adolescents living in developing and low-income countries are more likely to face nutritional challenges. Poor nutritional status during adolescence is an important determinant of health outcomes. Objective: To analyze the nutritional status (BMI based) of school-going adolescents in Gojra city, Punjab, Pakistan. Methods: A school-based cross-sectional survey was carried out covering 635 (6-8 grade) school-going adolescents (boys and girls) from public schools in Gojra city. Data were collected through anthropometric measures taken. Symptoms of malnutrition were also assessed. Mean and frequencies were reported for demographic variables and symptoms of malnutrition while two sample Independent T-test was used to compare the means of groups under study using SPSS version-23. Results: The overall prevalence of underweight in boys was found (33.9%) as compared to adolescent girls (32.3%). It was also found that malnutrition and related health complications were higher in adolescents with lower BMI values. Conclusions: Adolescent boys and girls were found with a high prevalence of malnutrition along with other symptoms. Adolescence is the make-or-break stage of life. Major physical, mental, and psychological growth takes place at this age. Adequate and balanced nutrition is a vital requirement to support this phase. Adolescents living in developing and low-income countries are more likely to face nutritional challenges. Poor nutritional status during adolescence is an important determinant of health outcomes. Objective: To analyze the nutritional status (BMI based) of school-going adolescents in Gojra city, Punjab, Pakistan. Methods: A school-based cross-sectional survey was carried out covering 635 (6-8 grade) school-going adolescents (boys and girls) from public schools in Gojra city. Data were collected through anthropometric measures taken. Symptoms of malnutrition were also assessed. Mean and frequencies were reported for demographic variables and symptoms of malnutrition while two sample Independent T-test was used to compare the means of groups under study using SPSS version-23. Results: The overall prevalence of underweight in boys was found (33.9%) as compared to adolescent girls (32.3%). It was also found that malnutrition and related health complications were higher in adolescents with lower BMI values. Conclusions: Adolescent boys and girls were found with a high prevalence of malnutrition along with other symptoms.